Proses Penanganan Perkara Pembunuhan Bayi Oleh Ibu Kandung Di Kota Surakarta - Pradiksa, Detami; , Hartanto, S.H, M.Hum (2017)
Currently, many found cases of infanticide committed by his own biological mother. Infanticide requires the baby killed shortly after birth. If the conditions are not fulfilled then it cannot be called infanticide by the biological mother, otherwise it is including ordinary murder or abortion. Infanticide by the biological mother is divided into two (2) type there are planned and not planned. This research using empirical juridical approach by collecting and examining secondary data and then followed by analyzing primary data obtained from the field. To reinforce the elements of Article were indicted based on the crime scene, the results of a post mortem and the testimony of witnesses. Law enforcement authorities in processing the cases of infanticide by the biological mother have a barrier related to witnesses and perpetrators.